EMPOWERING BUNGUS FISHING COMMUNITIES' ECONOMY THROUGH MARKETPLACE OPTIMIZATION AND DIGITAL MARKETING - Nuraeni Dahri; Danyl Mallisza; Jusmita Weriza; Wahyuni Yahyan; M.Ilham A.Siregar; Harry Setya Hadi; Dina adawiyah; Agus Sutradjo; Jhon Rinaldo; Doris yadewani; Delori Nancy Meyla; Nur Adilah; Fauzia Zainin (Ikatan Dosen Menulis, 2026)
This community service program addresses the limited market access faced by micro, small, and medium enterprises (MSMEs) among fishing communities in Bungus, Padang City, whose members produce processed fishery goods such as shredded fish floss (abon) and vacuum-packed fish products but continue to rely heavily on conventional, geographically limited sales channels. The program aimed to optimize the use of marketplace platforms, namely Shopee and Tokopedia, together with digital marketing strategies, in order to expand market reach and increase the income of partner MSMEs. The implementation adopted a Community-Based Empowerment approach carried out through three main stages: digital literacy socialization comparing e-commerce and marketplace systems, technical training in online store registration, smartphone-based product photography, and airtight packaging standardization, and continuous mentoring covering store management, promotional feature optimization, and digital transaction handling. Involving twenty-five partner MSMEs, the program produced a measurable increase in partner understanding of marketplace operations, the establishment of twelve official online stores, improved visual quality of product photography and packaging, and an average sales increase within two months following store optimization. These outcomes indicate that structured digital marketing mentoring is an effective pathway for expanding the market share of coastal MSMEs and strengthening their transition toward digitally based economic independence. The program also identified several implementation constraints, including varying levels of digital readiness among partners and the need for continued post-program mentoring, which are discussed as considerations for future coastal community empowerment initiatives.